Pengaruh Kombinasi Ekstrak Etanolik Temulawak (Curcuma canthorrizha Roxb) Rendah Minyak Atsiri dan Ekstrak Etanolik Sambung Nyawa (Gynura procumbens (Lour.) Merr) Terhadap Kadar Trigliserida Tikus Putih Jantan Galur Wistar Serta Gambaran Histopatologinya - Novianto, Agil (Jurnal Farmasi (Journal of Pharmacy), 2012)
Hyperlipidemia is factor affected to coronary hearth disease, allow with increase of serum level cholesterol and tryglycerida. This research is to know effect combination of ethanolic extract of Curcuma xanthorrizha Roxb with low content of volletile oil and ethanolic extract Gynura procumbens (Lour.) on triglyceride level serum and its hyperlipidemia manifestation atherosclerosis. Forty eight male albino rat devide into 8 groups. Positive group receive gemfibrozil, CMC-Na 0,5 % (negatif) and treatment group combination of temulawak and sambung nyawa 100:0, 75:25, 50:50, 25:75, 0:100. Dose of ethanolic extract temulawak is 225 mg/kg BB and dose of ethanolic exstrac sambung nyawa 150 Methode of this research by give diet lipid and yolk egg for about 30 day on treatment group except normal group after this give sample test for about 30 day. Trygliceride level serum measure on day 0 (baseline), 30 and 60 with Trigliserida FS Diasys®. Hypotrigliceride activity describe into % of change triglyceride level and analyse with Mann-whitney with level of significane 95 %. Histopatology analyze used cardiac aorta. Hypotriglyceride activity combination of extract temulawak and extract sambung nyawa showing no significance difference both combination (p>0,05). Combination of temulawak:sambung nyawa (75:25) give the highest hypotrigliceride activity with decrease on triglyceride level serum for about 56,77 %. Combination both extract effective to avoid atherosclerosis